Presbicia y su relación con la disminución de la agudeza visual de cerca en adultos mayores en la óptica soluciones visuales, del cantón Babahoyo. Primer semestre del 2018. - Morales Moreno, Katherinne Estefania (2018)
Presbyopia, also known as tired eyesight, is a visual defect that consists in diminishing the focusing ability of the eye. When the eye can not clearly focus on the images, the result is blurred vision. It should be borne in mind that presbyopia is not a disease, but a symptom caused by the natural course of aging that causes the eye's lens to lose its flexibility. As the lens becomes less flexible and less able to change shape as easily as before, the eye has a greater difficulty focusing on nearby objects. The first signs are usually perceived between 40 and 50 years. Above 40 it becomes more and more manifest, until the accommodation reaches its minimum by 65 years. The treatment of eyestrain or presbyopia is to correct this loss of accommodation of vision. The general objective of this research was to determine the relationship between presbyopia and visual acuity reduction in older adults in the Visual Solutions Optics of the Babahoyo canton, the first semester of 2018, which was developed under the non-experimental modality with a type of direct-descriptive-explanatory observation, taking as a study population 95 elderly adults with problems of visual acuity decrease close up, which were diagnosed and evaluated by the jaeger card in the data collection made with the questionnaire instrument With pre-prepared questions, the result was that patients attending Optical Visual Solutions, 50% suffer from presbyopia, so it is considered appropriate to use positive lenses, having as an alternative proposal to give visual health talks related to the presbyopia, in order to correct in time, while in more severe cases it is advisable to ophthalmology and / or more advanced treatments with specialists.